Meta-Analysis: Effects of Unsafe Action and Work Experience on Occupational Exposure to Needlestick Injury among Health Workers in the Hospital - Andriani, Nurul Dwi; Sumardiyono, Sumardiyono; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Needlestick injury is a dangerous work accident that causes blood contact with pa-tients and is at risk of being infected with blood borne diseases such as hepatitis B virus (HBV), hepatitis C (HCV), and human immunodeficiency virus (HIV). The purpose of this study was to analyze the influence of unsafe behavior factors on the incidence of accidents due to needlestick injury to health workers in hospitals. Subjects and Method: This research was conducted using a systematic review and meta-analysis study design using PICO, population: health workers, intervention: unsafe action and lack of work experience. Comparison: safe action and good work experience, Outcome: Needlestick Injury (NSI) incident. The articles used in this study came from 4 databases, namely Pubmed, ScienceDirect, ProQuest and Google scholar. The keywords of the article are (